2022
DOI: 10.21203/rs.3.rs-1970806/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of musculoskeletal disorders among taxi drivers in Yaoundé, Cameroon: Preventive effect of physical activity

Abstract: Background: Musculoskeletal Disorders (MSDs) are very common conditions in the workplace. Among professional drivers, there would be an increased risk of developing these affections. Identifying the associated factors would help to better devise effective prevention strategies. Our objective was to determine the prevalence of MSDs among taxi drivers in the city of Yaoundé and to study the associated factors, mainly the physical activity level. Methods: We conducted an analytical cross-sectional study of 151 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…6 Lower back pain is very common among truck, bus and taxi drivers and is one of the most commonly reported occupational health problems among professional drivers. 7 The magnitude of LBP among taxi drivers has been reported in different studies, such as Iran, 51.2%, 8 Ghana, 34.3%, 9 Taiwan, 51%, 10 Saudi Arabia, 60.7%, 11 Cameron, 72.8%, 12 China, 54%, 13 Hungary, 61.36%, 14 Turkey, 49.7%, 15 Addis Ababa, Ethiopia, 64.2%, 16 Tigray, Ethiopia, 27.9%. 17 A number of studies have identified a wide range of factors associated with LBP in taxi drivers.…”
Section: Introductionmentioning
confidence: 96%
“…6 Lower back pain is very common among truck, bus and taxi drivers and is one of the most commonly reported occupational health problems among professional drivers. 7 The magnitude of LBP among taxi drivers has been reported in different studies, such as Iran, 51.2%, 8 Ghana, 34.3%, 9 Taiwan, 51%, 10 Saudi Arabia, 60.7%, 11 Cameron, 72.8%, 12 China, 54%, 13 Hungary, 61.36%, 14 Turkey, 49.7%, 15 Addis Ababa, Ethiopia, 64.2%, 16 Tigray, Ethiopia, 27.9%. 17 A number of studies have identified a wide range of factors associated with LBP in taxi drivers.…”
Section: Introductionmentioning
confidence: 96%